UPAYA MENINGKATKAN AKREDITASI PUSKESMAS KE TINGKAT UTAMA DI UPT PUSKESMAS SARIMATONDANG KECAMATAN SIDAMANIK KABUPATEN SIMALUNGUN TAHUN 2020 - Yani Fridiana Saragih (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
ABSTRACT Community health center accreditation is an obligation as stipulated in Minister of Health Regulations of Republic Indonesia No. 46 of 2015 in an effort to improve the quality of health services. Not all Community health center have the same ability to fulfill accreditation standards in achieving accreditation status. The purpose of this study was to increase the accreditation of Community health center to the primary level at Service Unit of Community health center Sarimatondang, Sidamanik Sub District, Simalungun District. This type of research is a case study research with a qualitative approach. The research location was in Community health center Sarimatondang and the research period began in December 2019 until April 2020. The number of informants consisted of 8 Chairpersons of Public Health Efforts, Chair of Accreditation Quality, Head of Community health center, Midwife, Staff, Chair of Public Health Personal, Head of Environment-VII Sarimatondang, and Chairperson Admin. Data collection is done through in-depth interviews, document review and observation. Data is analyzed to make it easier to see data more simultaneously. The results showed that the average achievement score of Chapter IX accreditation standards was 76.82%. Achievement scores of Community health center accreditation standards for Chapter I, Chapter II, Chapter IV, and Chapter V ≥ 75%, Chapter VII and Chapter VII > 60%, and Chapter III, Chapter VI and Chapter IX > 20%. Inhibiting factors in the implementation of accreditation standards fulfillment at Sarimatondang Community health center include financial resources, variations in the level of education of human resources of Community health center staff and integrated service center cadres, staff assigned as program managers not in accordance with their main tasks and functions, limited time from the accreditation advisory team providing guidance and direction in preparation for accreditation. Efforts to improve the status of accreditation from Middle to Main, the Community health center Sarimatondang must improve the achievements of the scores of Chapter I, Chapter II, Chapter IV, Chapter V, Chapter VII, and Chapter VIII ≥ 80%; and the total achievements of Chapter III, Chapter VI, and Chapter IX ≥ 60%. It is recommended that the accreditation team that has been formed can maximize its activities to coordinate activities, conduct meetings discussing the obstacles faced in fulfilling accreditation, monitoring and evaluation standards to fit the tasks and functions. The accreditation team increases collaboration with external parties to help solve the problem of meeting accreditation standards and works based on the timeline to make the stages of activities that need to be carried out until the fulfillment of accreditation standards can be achieved when accreditation activities will begin.